Effect of Terrigenous Sediment Addition on the Generation of Arc Silicic Magma: Constraints From the Comparative Partial Melting Experiment at 1.5 GPa - Zang, Chunjuan; Wang, Mingliang (Frontiers in Earth Science, 2022)
To assess the effects of sediment addition on partial melting of subducted oceanic crust and generation of of arc silicic magma, a series of comparative partial melting experiment on a garnet plagioamphibolite and a 90 wt. % garnet plagioamphibolite + 10 wt. % plagioclase slate mixture at 850~1000℃ / 1.5GPa were conducted on a Piston-cylinder apparatus. In the experimental products, partial melt coexists with Amp+Pl+Grt+Cpx at 850~950℃ and Grt+Cpx+Pl at1000℃. Compared with pure garnet plagioamphibolite, partial melting of mixture get a higher melting percentage and generates the silicic melt with geochemical characteristics of higher Na2O/ K2O and lower Al2O3 in major element and high Rb content in trace element at over 950℃. This results indicate that silicic arc magma may generates from partial melting of metamorphic subducted oceanic crust with sediments thereon, sediment addition contribute to their chemical component and generation dynamic process.